2023
DOI: 10.1111/imb.12850
|View full text |Cite
|
Sign up to set email alerts
|

Uric acid metabolism promotes apoptosis against Bombyx mori nucleopolyhedrovirus in silkworm, Bombyx mori

Abstract: The white epidermis of silkworms is due to the accumulation of uric acid crystals. Abnormal silkworm uric acid metabolism decreases uric acid production, leading to a transparent or translucent phenotype. The oily silkworm op50 is a mutant strain with a highly transparent epidermis derived from the p50 strain. It shows more susceptibility to Bombyx mori nucleopolyhedrovirus (BmNPV) infection than the wild type; however, the underlying mechanism is unknown. This study analysed the changes in 34 metabolites in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Uric acids, the final metabolite in purine metabolism, was up-regulated to 1.32, 1.59, and 2.56 fold changes in the NCC, IAPV, and IAPV-NCC groups, respectively, compared to the control group (Table S2). Uric acid is an essential antioxidant for survival and makes a substantial contribution to longevity and immunity in mammals and insects. , It has been reported that uric acid metabolism promotes the immune pathway, such as apoptosis, against Bombyx mori nucleopolyhedrovirus in silkworm . These results suggested that purine metabolism is critical for IAPV infection, and JNCC can promote the content of uric acid in purine metabolism.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Uric acids, the final metabolite in purine metabolism, was up-regulated to 1.32, 1.59, and 2.56 fold changes in the NCC, IAPV, and IAPV-NCC groups, respectively, compared to the control group (Table S2). Uric acid is an essential antioxidant for survival and makes a substantial contribution to longevity and immunity in mammals and insects. , It has been reported that uric acid metabolism promotes the immune pathway, such as apoptosis, against Bombyx mori nucleopolyhedrovirus in silkworm . These results suggested that purine metabolism is critical for IAPV infection, and JNCC can promote the content of uric acid in purine metabolism.…”
Section: Resultsmentioning
confidence: 91%
“…Uric acid is an essential antioxidant for survival and makes a substantial contribution to longevity and immunity in mammals and insects. 51,52 It has been reported that uric acid metabolism promotes the immune pathway, such as apoptosis, against Bombyx mori nucleopolyhedrovirus in silkworm. 52 These results suggested that purine metabolism is critical for IAPV infection, and JNCC can promote the content of uric acid in purine metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that the UA metabolic pathway inhibits the proliferation of BmNPV by activating the apoptotic pathway (Su et al, 2023); however, the function of MoCoS , one of the key genes in this pathway, is unknown. In this study, we have validated the pivotal function of BmMoCoS in facilitating BmNPV infection, primarily attributed to its regulatory role in the UA pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has demonstrated that the disruption of BmMoCoS expression results in oily traits in silkworm (Fujii et al, 2016). These oily silkworms exhibit heightened susceptibility to BmNPV, and UA has been found to activate apoptosis, thereby impeding BmNPV infection (Su et al, 2023). However, thus far, no direct evidence has been provided to establish the link between BmMoCoS and UA metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation